Integrated Erp And Web Aplication Through Ipman (Integrated Port Time Management) - Yessica Ratri Wiguna (Cakrawala Repositori IMWI, 2023)
Era Internet of things has become an everyday life that should be a usual things. Company need to see this as a usual and always keep up so it wont left behind by their competitor. Logistic and supply chain management is of the key when an industry has a production plant and also a marketing because it can control from upstream untill downstream. Supply chain management is becoming a critical issue that the company have to get the best way to get more efficient supply chain. Shipping and port industry have growth to be a global operator to give services around the world. Port management also needed to be managed because the shorter time of ship in the port, the activity could get more and it will give more efficient cost for the terminal. Port time has a direct relation to oil bunker consumption which is if the ship/vessel can minimize their port time, bunker consumption also become lower then the emission also lower. Supply chain management could connect with a system that manage and plan company resources including funds, time, machine, tools, etc., then supply chain management could go digital. ERP looked complicated because it is an integrated concept of planning and managing company resources. When the ERP become too complex, the company could make a ‘bridge’ that can be a hub to connect a different website or application , so , the data will store in the same server and analysis could be done faster.